2010
DOI: 10.1007/s12665-010-0482-x
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional horizontal modeling of fine-sediment transport at the South Channel–North Passage of the partially mixed Changjiang River estuary, China

Abstract: Tidal flow and fine-sediment transport at the South Channel-North Passage of the partially-mixed Changjiang River estuary were studied using a twodimensional horizontal (2DH) numerical model. This 2DH model was achieved by depth-integrating the momentum and convection-diffusion equations. The Alternating Direction Implicit scheme was used to solve the governing equations. The iterative method was adopted for the calculation of convection and diffusion terms of momentum equation. Comparisons between calculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…Shi [] used a one‐dimensional vertical model to study the fine suspended sediment distribution at the South Channel‐North Passage of the partially mixed YRE. Subsequently, a two‐dimensional numerical model was established to study the characteristics of tidal flow and suspended sediment concentration in the same region [ Shi et al ., ]. However, the depth‐integrated momentum and convection‐diffusion equations are unable to fully account for the effect of the complex topographic variations and baroclinic hydrodynamics in the YRE.…”
Section: Introductionmentioning
confidence: 99%
“…Shi [] used a one‐dimensional vertical model to study the fine suspended sediment distribution at the South Channel‐North Passage of the partially mixed YRE. Subsequently, a two‐dimensional numerical model was established to study the characteristics of tidal flow and suspended sediment concentration in the same region [ Shi et al ., ]. However, the depth‐integrated momentum and convection‐diffusion equations are unable to fully account for the effect of the complex topographic variations and baroclinic hydrodynamics in the YRE.…”
Section: Introductionmentioning
confidence: 99%
“…Then, a 2D vertical integrated model was used to simulate, and subsequently to investigate the characteristics of tidal flow and suspended sediment concentration at this channel [69]. From these studies it was observed that new features had formed after the finalization of the shipping channel; however, the model used did not include the baroclinic component, which is an important factor in the transport of sediment.…”
Section: Yangtze River and The Shanghai Port In The East China Seamentioning
confidence: 99%
“…These requirements challenge almost all existing 2D or 3D numerical models [9]. As a result, in real applications of the Yangtze Estuary, researchers often have to use coarse grids, establish local models [10][11][12], or adopt simplified methods, such as the method of the morphological scale factor [13,14]. In this paper, an efficient 2D numerical model is developed to simulate the tidal flow, sediment transport, and riverbed evolution in the Yangtze Estuary using a high-resolution channel-refined unstructured grid.…”
Section: Introductionmentioning
confidence: 99%